Analysis of the Influence of Democracy Index, Human Development Index, Foreign Investment, Government Expenditure, and Labor on Indonesian Economic Growth - Muhammad Ivan Fadillah; Zainuri; Sebastiana Viphindrartin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Economic growth is one of the main indicators of the economic progress of a region or country. The economic performance of a country is determined by the economic policies implemented by the government, the environment in which the economy operates, and the political economic system it implements. Many non-economic factors ultimately affect the economic activities of a country. This study aims to determine whether the Indonesian Democracy Index, Human Development Index, Foreign Investment, Government Expenditure, and Labor partially affect Indonesia's economic growth. The analysis method used is multiple linear regression using Eviews10. The results of the study indicate that the Democracy Index and Human Development Index do not have a significant effect on Economic Growth. While Foreign Investment, Government Expenditure and Labor have a significant effect on Economic Growth.